Management of Indonesia ICT Business Incubators: Administrators’ Compared to Tenants’ Perspecive - Emyana Ruth Eritha Sirait; Faiq Wildana (Center for Science and Technology Development Studies, Indonesian Institute of Sciences, 2017)
Business incubation is one of entrepreneurship development methods believed to have advantages compared with other SME development patterns. The model used in managing the business incubators is influenced by the business focus of the participants/tenants. In managing the ICT business incubators, there are some key factors slightly different from the management of others. However, the legal rules and standards for organizing various types of incubators are still equated. It is concerned that there will be some misunderstandings/misleading from the administrators or managers in providing their services, so that the process fails to reach its main objectives. This study has surveyed some managers of ICT incubators to get their perspectives about the dominant aspects among 8-S mandatory services by using Analytical Hierarchy Process, and also some tenants about their satisfaction to incubators services. The result is then reviewed based on ICT product and business characteristics. Keywords: ICT Business Incubators, Management, Analytical Hierarchy Process, Customer Development Model.